O-21 Advance care planning in palliative care: A systematic literature review of the contextual factors influencing its uptake. (1st September 2015) - Lovell, Allison; Yates, P
Abstract : Background: Advance Care Planning (ACP) is an iterative process of discussion, decision-making and documentation about end-of-life care. ACP is highly relevant in palliative care due to intersecting clinical needs. To enhance its implementation within health systems the contextual factors influencing its uptake need to be better understood. Aim: To identify the contextual factors influencing the uptake of ACP in palliative care as published between January 2008 and December 2012. Methods: Databases were systematically searched for studies about ACP in palliative care published between January 2008 and December 2012. This yielded 27 eligible studies, which were analysed to identity themes. Results: Factors associated with greater uptake included older age, a diagnosis of cancer, greater functional impairment, greater understanding of poor prognosis and receiving or working in specialist palliative care. Barriers included having non-malignant diagnoses, having dependent children and uncertainty about ACP and its legal status. Individuals' previous illness experiences, preferences and attitudes also influenced their participation in ACP. Discussion: This review demonstrated that access to ACP is not equal for all patients. While attempts have been made to implement health system wide ACP programs care needs to be taken, however, to acknowledge the complexity and sensitivities surrounding ACP. Conclusion: Factors influencing the uptake of ACP in palliative care are complex and multifaceted reflecting the diverse and often competing needs of patients, health professionals, legislature and health systems. Large population-based studies of palliative care patients are required to develop the sound theoretical and empirical foundation needed to improve uptake of ACP in this setting.